Apollo 11 [videorecording (DVD)] - Aldrin, Buzz; Armstrong, Neil, 1930-2012; Collins, Michael, 1930-2021-; Archer, Joan Ann; Armstrong, Janet, 1934-2018 (Universal Pictures Home Entertainment, 2019)
From director Todd Douglas Miller comes a cinematic event 50 years in the making. Crafted from a newly discovered trove of 65mm footage, and more than 11,000 hours of uncatalogued audio recordings, the film takes viewers straight to the heart of NASA's most celebrated mission, the one that first put men on the moon, and forever made Neil Armstrong and Buzz Aldrin into household names.